Gap Analysis and Economic Viability of Front-line Demonstrations in Indian Mustard (Brassica juncea L.) under Hyper Arid Partial Irrigated Zone of Rajasthan - Shivran, R. K.; Singh, Ummed; Kishor, Naval; Kherawat, Bhagwat Singh; Pant, Richa; Mehra, Keshav (International Journal of Bio-resource and Stress Management, 2020)
Performance analysis in terms of gap analysis, yield enhancement and economic viability of improved production technologies of Indian mustard vis-à-vis farmers’ practice was evaluated through front-line demonstrations at farmers’ field during rabi seasons (October to March) of respective years, 2013-2014 to 2018-2019. The front-line demonstrations were conducted by Krishi Vigyan Kendra, Bikaner-II, Rajasthan. Newly released improved varieties of Indian mustard viz., RGN 48, RGN 229 and DRMRIJ 31 were grown under demonstrations. The experimental results envisage that average yield under demonstration ranged from 1550 to 2600 kg ha-1 with a mean of 2154 kg ha-1. In per cent terms, scaling in productivity following improved technology ranged from 14.81 to 33.33% with an average value of 25.89% (over the Farmers’ practice). Moreover, the grain yield also recorded substantially higher under demonstrations (2154 kg ha-1) over district average (1122 kg ha-1) and state average (1427 kg ha-1). The average yield gaps for technology, extension and technology index were 655, 443 kg ha-1 and 22.90 per cent, respectively. Demonstration of improved technologies also enhanced average gross (Rs. 76,318 ha-1), net return (Rs. 50,740 ha-1), effective gain (Rs. 12,393 ha-1) and additional return (Rs. 14,107 ha-1) in comparison to Farmers’ practice. This resulted in realizing higher incremental cost benefit ratio (8.23) and benefit: cost ratio (2.95) compared to the Farmers’ practice (2.50) during six years study period. This enhancement in grain yield and economics of chickpea under demonstrations clearly showed the impact of adoption of improved technology over farmers’ practice in Hyper Arid Partial Irrigated Plain Zone of Rajasthan.